2002
DOI: 10.1038/modpathol.3880505
|View full text |Cite
|
Sign up to set email alerts
|

Aneusomy 17 in Breast Cancer: Its Role in HER-2/neu Protein Expression and Implication for Clinical Assessment of HER-2/neu Status

Abstract: HER-2/neu protein overexpression in breast cancer is mostly caused by HER-2/neu gene amplification. However, it is unclear whether aneusomy 17 may also play a role. Using immunohistochemistry assay (IHC) with DAKO antibody and manual quantitation, 189 specimens were selected from archival invasive breast cancer specimens, including most IHC-positive and some IHC-negative cases (n ‫؍‬ 158 and 31, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
72
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 17 publications
12
72
0
Order By: Relevance
“…There have been several reports that cases with HER-2 overexpression without gene amplification mostly occurred in moderate positive cases (2 þ ) (Perez et al, 2002;Varshney et al, 2004), in line with this study. Various explanations of this discrepancy have been proposed: transcriptional or post-translational activation (Slamon et al, 1989), artifactual high sensitivity of IHC (Varshney et al, 2004), the presence of chromosome 17 polysomy (Wang et al, 2002) or the low detection rate of FISH analysis (Jacobs et al, 1999). We found one case of polysomy in 2 þ patients and two cases of polysomy in 1 þ patients, suggesting that the presence of chromosome 17 polysomy might be one explanation for the discrepancy between the HercepTest and FISH in oesophageal SCC.…”
Section: Discussionmentioning
confidence: 61%
“…There have been several reports that cases with HER-2 overexpression without gene amplification mostly occurred in moderate positive cases (2 þ ) (Perez et al, 2002;Varshney et al, 2004), in line with this study. Various explanations of this discrepancy have been proposed: transcriptional or post-translational activation (Slamon et al, 1989), artifactual high sensitivity of IHC (Varshney et al, 2004), the presence of chromosome 17 polysomy (Wang et al, 2002) or the low detection rate of FISH analysis (Jacobs et al, 1999). We found one case of polysomy in 2 þ patients and two cases of polysomy in 1 þ patients, suggesting that the presence of chromosome 17 polysomy might be one explanation for the discrepancy between the HercepTest and FISH in oesophageal SCC.…”
Section: Discussionmentioning
confidence: 61%
“…[10][11][12][13] In a recently published series by Vanden Bempt et al, >40% of breast carcinomas were found to harbor increased CEP17 copy number.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, the reported frequency of CEP17 copy number alteration in breast cancer varies, depending on the study population, selection criteria, and the definition of chromosome 17 polysomy (CEP17). [10][11][12][13] In the literature, it is commonly assumed that an increase in CEP17 copy number is because of polysomy 17, and these terms have been used interchangeably. However, it is important to recognize that an increase in CEP17 signals does not necessarily represent a true polysomy (ie, gain of the entire chromosome), but rather may represent a focal pericentromeric gain or a partial polysomy.…”
mentioning
confidence: 99%
“…The cutoff number for determining oncogene amplification by CISH was empirically defined as six copies per cell based on the observation that most cases with polysomy of chromosome 17 fall into three to five signals per nucleus. 12,17 However, aneusomy of chromosome 17 is common in breast cancer 12,18,[21][22][23][24] and polysomy with 45 copies of chromosome 17 per nucleus is not rare. 17 These cases would be scored erroneously as low amplification while there is no actual amplification present.…”
Section: Discussionmentioning
confidence: 99%